Analysis of innovation adoption decision process among the mechanised fishing boat operators at selected fishing harbours in India - Charles Jeeva, J.; Balasubramaniam, S.; Vasanthakumar, J. (Indian Journal of Fisheries, 2016)
The study was conducted among the large mechanised wooden trawl boat operators involved in marine fishing in three selected major fishing harbours of the country viz., Visakhapatnam in Andhra Pradesh, Thoothukudi in Tamil Nadu and Veraval in Gujarat. The socio-economic and psychological characteristics of fishermen were assessed. The overall innovation decision efficiency index (IDEI) score was 55.25%. The findings on centre-wise and technology-wise IDEI scores are also discussed. The respondents from the three fishing centres differed significantly (p